Painting the Landscape. The Landscape that Makes Us Think - Valagussa, Francesco (Aisthesis, 2025)
The article aims to show how landscape is not a natural datum but a typically modern cultural product, particularly linked to the importance that the subject’s point of view has managed to gain over the last few centuries. Using examples taken from Dante, Vico, Cézanne, Simmel and Merleau-Ponty, the article shows how the construction of landscape depends on the presence of a mental image. Such an image, already previously acquired through arts such as painting or poetry, has the effect of gathering and collecting a series of elements, giving them that unity without which it is not possible to speak of landscape. After showing how important the cultural dimension is for the creation of landscape, the second part of the article shows how landscape can in turn become a model for art. From this reciprocal interaction between the two levels, it is possible to rethink the relationship between landscape and environment.